What is a solution to the differential equation #dy/dt=e^t(y-1)^2#?

Answer 1

The General Solution is:

# y = 1-1/(e^t + C) #

We have:

# dy/dt = e^t(y-1)^2 #

We can collect terms for similar variables:

# 1/(y-1)^2 \ dy/dt = e^t #

Which is a separable First Order Ordinary non-linear Differential Equation, so we can "separate the variables" to get:

# int \ 1/(y-1)^2 \ dy = int e^t \ dt #

Both integrals are those of standard functions, so we can use that knowledge to directly integrate:

# -1/(y-1) = e^t + C #
And we can readily rearrange for #y#:
# -(y-1) = 1/(e^t + C) #
# :. 1-y = 1/(e^t + C) #

Leading to the General Solution:

# y = 1-1/(e^t + C) #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#y=-1/(e^t+C)+1#

This is a separable differential equation, which means it can be written in the form:

#dy/dx*f(y)=g(x)#

It can be solved by integrating both sides:

#int\ f(y)\ dy=int\ g(x)\ dx#
In our case, we first need to separate the integral into the right form. We can do this by dividing both sides by #(y-1)^2#:
#dy/dt*1/(y-1)^2=e^tcancel((y-1)^2/(y-1)^2)#
#dy/dt*1/(y-1)^2=e^t#

Now we can integrate both sides:

#int\ 1/(y-1)^2\ dy=int\ e^t\ dt#
#int\ 1/(y-1)^2\ dy=e^t+C_1#
We can solve the left hand integral with a substitution of #u=y-1#:
#int\ 1/u^2\ du=e^t+C_1#
#int\ u^-2\ du=e^t+C_1#
#u^-1/(-1)+C_2=e^t+C_1#

Resubstituting (and combining constants) gives:

#-1/(y-1)=e^t+C_3#
Multiply both sides by #y-1#:
#-1=(e^t+C_3)(y-1)#
Divide both sides by #e^t+C_3#:
#-1/(e^t+C_3)=y-1#
#y=-1/(e^t+C)+1#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

The solution to the given differential equation ( \frac{dy}{dt} = e^t(y-1)^2 ) is ( y(t) = 1 + \frac{1}{Ce^{-t} - 1} ), where ( C ) is an arbitrary constant.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7